Appointment of Mr. Enrico Cordero - De La Salle University, Manila (Animo Repository, 2006)
DLSU-Manila Executive Vice President Dr. Carmelita I. Quebengco announced the appointment of Mr. Enrico Cordero as AVP for Campus Services, effective May 16, 2005. Mr. Cordero oversees the operations of the following: Materials Reproduction and Distribution Office, Medical and Dental Services, Purchasing Office, Warehouse and Inventory Management Office and Mailing.